Association of Dyslipidemia with Severity of Meibomian Gland Dysfunction and Type of Dry Eye Disease - Rofiq, Rofiqi; Aldina, Rosy; Mandrasari, Yurike; Holipah, Holipah; Prayitnaningsih, Seskoati (eJournal Kedokteran Indonesia, 2025)
The meibomian gland is physiologically involved in lipid secretion; thus, abnormalities in systemic lipid levels may be related to meibomian gland lipid secretion. Meibomian gland dysfunction (MGD) has been strongly associated with dry eye disease (DED), especially the evaporative type. The MGD has been known to increase cholesterol levels, mainly cholesterol ester, in meibomian gland secretions, which is associated with the pathology of MGD. The aim of the study is to assess the association of dyslipidemia with MGD and DED. This was a cross-sectional population-based study using consecutive sampling. Data was taken from the database of the Smart Health Study conducted in Mendalanwangi, Sidorahayu, and Cepokomulyo Village, Malang, from July to November 2019. There were 867 subjects aged ≥40years old with risk of MGD. Assessment of DED ocular surface disease index (OSDI) score, tear breakup time (TBUT), Tear Meniscus (TM), MGD, and dyslipidemia (level of Triglycerides (TG) and High-Density Lipoprotein (HDL)) was performed. The majority of subjects were female with no DED or dyslipidemia. Most respondents had MGD grade 1. Patients with dyslipidemia had a 1.4-fold risk for evaporative dry eye (EDE) compared to patients with normal lipid levels [OR 1.417 (95% CI: 1.0-2.070)]. Patients with MGD had a lower risk of aqueous deficiency dry eye (ADDE) [OR 0.160 (95% CI: 0.699 – 0.366)]. There was no significant association between dyslipidemia and MGD and DED. Patients with dyslipidemia had a 1.4-fold risk of EDE compared to patients with normal lipid levels.